Public Perception of Genetically Modified Organisms (GMOs) in Poland Based on the Samples of Selected Groups of People - Nowakowska, Justyna Anna; Berezovska, Daria; Szulińska, Aleksandra (Studia Ecologiae et Bioethicae, 2021)
The present study investigated the level of knowledge and the attitude of citizens of Poland (n = 699), taking into account - sex, age, education, and the place of residence (city or countryside), towards the various uses of GMOs. The statistical analysis of the results was performed in STATISTICA 12. It has been shown that the knowledge of inhabitants about GMOs in Poland is growing, but the fear of genetically modified products is still present in over half of the population. Most women are concerned about GMOs, and pay more attention to the labelling of GMO products, but would not give them to their children. People under the age of 20 have a positive attitude towards GMOs, while people over the age of 35, emphasise the negative effects of consuming GMO products. Most people living in the countryside are afraid of GMO products, and the opinion of city residents is divided into two almost equal groups: both supporters and opponents of GMOs. Differences in responses to the fear of the negative effects of consuming GMO products were statistically significant (p < 0.001), and revealed that greater concern was present among people living in rural areas (67%), than among urban residents (49%). At the same time, almost an equal number of rural and urban residents (67%) were favourable to the use of genetically engineered drugs (p < 0.01).